A Potent Leukocyte Transmigration Blocker: GT-73 Showed a Protective Effect against LPS-Induced ARDS in Mice - Eliav Blum; Raanan Margalit; Laura Levy; Tamar Getter; Ron Lahav; Sofia Zilber; Paul Bradfield; Beat A. Imhof; Evgenia Alpert; Arie Gruzman (Molecules, 2021)
We recently developed a molecule (GT-73) that blocked leukocyte transendothelial migration from blood to the peripheral tissues, supposedly by affecting the platelet endothelial cell adhesion molecule (PECAM-1) function. GT-73 was tested in an LPS-induced acute respiratory distress syndrome (ARDS) mouse model. The rationale for this is based on the finding that the mortality of COVID-19 patients is partly caused by ARDS induced by a massive migration of leukocytes to the lungs. In addition, the role of tert-butyl and methyl ester moieties in the biological effect of GT-73 was investigated. A human leukocyte, transendothelial migration assay was applied to validate the blocking effect of GT-73 derivatives. Finally, a mouse model of LPS-induced ARDS was used to evaluate the histological and biochemical effects of GT-73. The obtained results showed that GT-73 has a unique structure that is responsible for its biological activity; two of its chemical moieties (tert-butyl and a methyl ester) are critical for this effect. GT-73 is a prodrug, and its lipophilic tail covalently binds to PECAM-1 via Lys536. GT-73 significantly decreased the number of infiltrating leukocytes in the lungs and reduced the inflammation level. Finally, GT-73 reduced the levels of IL-1β, IL-6, and MCP-1 in bronchoalveolar lavage fluid (BALF). In summary, we concluded that GT-73, a blocker of white blood cell transendothelial migration, has a favorable profile as a drug candidate for the treatment of ARDS in COVID-19 patients.